Presentation of "The Programme Director and the Teaching Excellence Framework: How do we train the former to survive the latter?" - Massie, Ruth (Cranfield University, 2018)
Presentation for Higher Education Academy's Annual Conference 2017. Massie, R., 2017, The Programme Director and the Teaching Excellence Framework: How do we train the former to survive the latter? , In HEA Annual Conference 2017 Generation TEF: Teaching in the spotlight, 4 th -6 th July 2017, University of Manchester, UK
Keywords: 'Programme Director'; 'Teaching Excellence Framework'; 'Higher Education'; 'Business and Management not elsewhere classified'; 'Organisational Behaviour'